2009
DOI: 10.1016/j.cell.2009.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanisms of Pain

Abstract: The nervous system detects and interprets a wide range of thermal and mechanical stimuli as well as environmental and endogenous chemical irritants. When intense, these stimuli generate acute pain, and in the setting of persistent injury, both peripheral and central nervous system components of the pain transmission pathway exhibit tremendous plasticity, enhancing pain signals and producing hypersensitivity. When plasticity facilitates protective reflexes, it can be beneficial, but when the changes persist, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
3,138
1
142

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 3,415 publications
(3,320 citation statements)
references
References 162 publications
39
3,138
1
142
Order By: Relevance
“…In our study the Aδ‐fibres were selected because main behavioural changes are related to tactile allodynia and hyperalgesia and they respond to mechanical stimulation (Basbaum et al., 2009) even better than C‐fibres. Our aim was to electrophysiologically study the changes in Aδ‐fibre activity and to determine if these changes were sensitive to the treatment with the σ1R antagonist.…”
Section: Discussionmentioning
confidence: 95%
“…In our study the Aδ‐fibres were selected because main behavioural changes are related to tactile allodynia and hyperalgesia and they respond to mechanical stimulation (Basbaum et al., 2009) even better than C‐fibres. Our aim was to electrophysiologically study the changes in Aδ‐fibre activity and to determine if these changes were sensitive to the treatment with the σ1R antagonist.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the close proximity of macrophages and nerves within lesions suggests that macrophage-derived cytokines may also contribute to pelvic pain in endometriosis by acting directly on nociceptors generating a pain response and hypersensitivity. 40,42 We have previously shown that estrogens can also act directly on human sensory neurons to increase the mRNA concentrations of key nociceptive ion channels, including TAC1, P2RX3, and TRPV1, 43 further supporting a role for estrogens in modulating pain response in endometriosis by acting on nerves.…”
Section: Endometriosis Is a Neuroinflammatory Disordermentioning
confidence: 91%
“…39 Macrophages are vital in the regeneration of damaged nerves after injury to the central nervous system and peripheral nervous system and, although infiltrating sensory nerves present within endometriosis lesions are not damaged per se, they may experience a chemical milieu similar to inflammation in response to trauma. 40 In a mouse model of acute peripheral nerve injury, an alternative macrophage response was detected, 41 and this phenotype has been associated with a sterile inflammatory environment similar to endometriosis. We suggest that the reciprocal relationship between macrophages and nerves encourages innervation of endometriosis lesions.…”
Section: Endometriosis Is a Neuroinflammatory Disordermentioning
confidence: 99%
“…The ability to detect and react to noxious environmental stimuli is a highly adaptive physiological response that is mediated through the coordinated processing of sensory information by the peripheral and central nervous systems [1][2][3][4]. Chronic pain in the presence or absence of tissue trauma is characterized by increased sensitivity to painful stimuli (i.e., hyperalgesia) and the perception of pain in response to normally innocuous stimuli (i.e., allodynia) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pain in the presence or absence of tissue trauma is characterized by increased sensitivity to painful stimuli (i.e., hyperalgesia) and the perception of pain in response to normally innocuous stimuli (i.e., allodynia) [4]. Based on many studies of the neurobiology of pain over the last 20 years, it is now appreciated that both peripheral and central neural pathways become "sensitized" in response to ongoing nociceptor stimulation [3].…”
Section: Introductionmentioning
confidence: 99%